Investigation and management of the long-term ventilated premature infant. (November 2018) - Wright, M.F.A.; Wallis, C.
Abstract: Bronchopulmonary dysplasia (BPD) is a common complication of prematurity, and despite significant advances in neonatal care over recent decades its incidence has not diminished. Although most affected infants have mild disease requiring a short period of oxygen supplementation or respiratory support, severely affected infants can become dependent on positive pressure support for a prolonged duration. In such cases, investigations should be carried out to ascertain whether there are secondary disease processes exacerbating the child's respiratory status. In case of established severe BPD, respiratory support with non-invasive or invasive positive pressure ventilation is required. In this paper we discuss the indications for, and practicalities of, the various modalities available. Potential cardiorespiratory sequelae of BPD include recurrent respiratory infections, childhood wheezing illnesses, abnormalities of lung structure and function, and pulmonary hypertension.